Dreams of Duneland : A Pictorial History of the Indiana Dunes Region - Schoon, Kenneth J. (Book collections on Project MUSE., 2013)
The towering sand dunes along Lake Michigan are one of the most unexpected natural features of Indiana. This book brings to life the remarkable story of this extraordinary place: the wide diversity of plant and animal species; and the long history of competition for the land among farmers, fur traders, industrialists, conservationists, and urban and recreational planners.